ANALYSIS OF THE METAPHORS IN TAYLOR SWIFT’S SONGS "DEAR JOHN" - Raya Arthatian; Nurul Fadhillah; Muhammad Ilham (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Humans use language to communicate and convey their ideas and feelings, which can be expressed as a song. Through its lyrics, a song expresses a concept or a mood. A song may contain many metaphors with contextual significance in order to portray a mood and emotion. Various people may have diverse interpretations of a song. This implies all types of songs, including Taylor Swift’s "Dear John". As a result, the metaphors that are employed in the song will be covered in this research. This song’s metaphors will be examined via Ullman’s metaphor theory. The method used in this research is descriptive qualitative. This method was selected because it provides the information required to address the research’s issues. Regarding the objectives of this study, it was discovered that this song has four metaphors: one synesthetic metaphor, three concrete to abstract metaphors, zero anthropomorphic metaphors, and zero animal metaphors. The purpose of using these metaphors is to help the listeners grasp the depths of emotions the songwriter aimed to portray in the song, in addition to helping the tale in the song be more captivatingly presented.